'We Are with You, Vietnam': Transnational Solidarities in Socialist Hungary, Poland and Yugoslavia. (July 2015) - Mark, James; Apor, Péter; Vučetić, Radina; Osęka, Piotr
Global solidarity with anti-imperialist struggles – which state socialist regimes in eastern Europe sought to inculcate in their populations from the 1950s onwards – constitutes a little studied form of modern transnational political socialization. This article explores this theme by analysing how three socialist countries – Hungary, Poland and Yugoslavia – attempted to build mass solidarity with the Vietnamese in the 1960s and 1970s. First, the article examines the political uses of transnationalism for socialist regimes in the 1960s, as the struggle for socialism in the so-called 'Third World', and support for such struggles in the West, allowed the socialist East to construct powerful images of a world turning towards its own political and moral values. Second, it explores how socialist citizens themselves re-interpreted transnational solidarity for their own ends, turning its language into a criticism of foreign policy, or state socialism at home; or using the opportunities it provided to challenge the state's right to control the public sphere. In doing so, the article suggests that we cannot understand such solidarity movements simply as top-down impositions from Moscow or national capitals; rather, they also reveal important aspects of state-society relations.